Cyberbiosecurity for Biopharmaceutical Products - Mantle, Jennifer L.; Rammohan, Jayan; Romantseva, Eugenia F.; Welch, Joel T.; Kauffman, Leah R.; McCarthy, Jim; Schiel, John; Baker, Jeffrey C.; Strychalski, Elizabeth A.; Rogers, Kelley C.; Lee, Kelvin H. (Frontiers in Bioengineering and Biotechnology, 2019)
Cyberbiosecurity is an emerging discipline that addresses the unique vulnerabilities and threats that occur at the intersection of cyberspace and biotechnology. Advances in technology and manufacturing are increasing the relevance of cyberbiosecurity to the biopharmaceutical manufacturing community in the United States. Threats may be associated with the biopharmaceutical product itself or with the digital thread of manufacturing of biopharmaceuticals, including those that relate to supply chain and cyberphysical systems. Here, we offer an initial examination of these cyberbiosecurity threats as they stand today, as well as introductory steps towards paths for mitigation of cyberbiosecurity risk for a safer, more secure future.